Blue Technology towards Sustainable Urban and Coastal Development - Kathijotes, Nicholas (My University, 2014)
The aim of Blue Economy models are to shift society from scarcity to abundance –based on what we have, and to start tackling issues that cause environmental and related problems through new and novel ways. Some major factors that cause ecological alterations to coastal and surface waters and contribute to nutrient inputs include, in no special order, municipal wastewater and storm water discharges; combined sewer overflows; other urban runoff; agricultural runoff; aquacultures, and various others. The issue of nutrient input due to aquaculture, being a serious input source in developing countries is emphasized together with actual measurements and control techniques applied in EU. Other key issues in coastal and aquaculture environments including Coastal Tourism, Marine Renewable Energy, Blue Biotechnology and Spatial Planning are presented within the scope of blue economy principle and thus suggesting novel actual management techniques.
Keywords: Blue economy; Nutrients; Fisheries; Sustainability; Tourism; Biotechnology